Animasi Cerita Wayang Sebagai Media Pembelajaran Bahasa Jawa - Aji, Gilang Baskoro; Waluyo, Retno (ICSE (Institute of Computer Sciences and Engineering), 2021)
Abstract: Javanese culture is one of the cultures that existed in Indonesia. One of the many Javanese culture is a puppet. The role of Education in preserving the Puppet that is by implementing subject puppet stories Junior High School syllabus in subjects of the Java language. Animated puppet stories